2021
DOI: 10.3390/f12081055
|View full text |Cite
|
Sign up to set email alerts
|

The Possibility of Regenerating a Pine Stand through Natural Regeneration

Abstract: Scots pine (Pinus sylvestris L.) is a widespread species in Eurasia, but its natural range can be significantly altered by a variety of stressors. The ability of pine to regenerate naturally is significantly reduced by its occurrence in unsuitable habitats. The processes of natural selection of pine from select habitats can be followed in stands of national parks where forestry activities are excluded. The possibility of pine regeneration is influenced by the following factors: characteristics of produced seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…To date, many Ukrainian scientists have studied the natural regeneration of pine after clearcut at different times (Fuchylo 2011;Maurer et al 2013;Levchenko, Mazurenko 2017;Maurer, Kimeichuk 2020) and foreign scientists (Dong et al 2003;Andrzejczyk, Żybura 2012;Dobrowolska 2015;Czyżyk 2017;Aleksandrowicz-Trzcińska et al 2018;Bílek et al 2018;Saursaunet et al 2018;Długosiewicz et al 2019;Przybylski et al 2021). Fuchylo (2011) described the abundant natural regeneration in the humid forests of Eastern Polissya.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, many Ukrainian scientists have studied the natural regeneration of pine after clearcut at different times (Fuchylo 2011;Maurer et al 2013;Levchenko, Mazurenko 2017;Maurer, Kimeichuk 2020) and foreign scientists (Dong et al 2003;Andrzejczyk, Żybura 2012;Dobrowolska 2015;Czyżyk 2017;Aleksandrowicz-Trzcińska et al 2018;Bílek et al 2018;Saursaunet et al 2018;Długosiewicz et al 2019;Przybylski et al 2021). Fuchylo (2011) described the abundant natural regeneration in the humid forests of Eastern Polissya.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies have shown that the amount of Scots pine undergrowth in different test areas after the irregular shelterwood cutting varies from 54 082 individuals•ha -1 to 182 703 individuals•ha -1 . There is evidence that the success of natural regeneration depends on many factors (Przybylski et al 2021), such as litter, competition with other plants and properties of the mineral soil. With an increase in litter thickness from 0.3 cm to 5.0 cm, the amount of pine regeneration decreases from 10.5 to 0.1 thousand individuals per ha (Levchenko, Mazurenko 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Aniszewska et al (2019) has shown that short microwave irradiation of initially closed Scots pine cones leads to their opening due to the rapid loss of moisture, and that viable seeds can be harvested from them. The process of initial opening is ecologically relevant, as it influences the dispersal of the mostly airborne seeds and, ultimately, the survival rate of seedlings (Winsa, 1995;Przybylski et al, 2021). As Pinus is widespread in the Northern Hemisphere, control of cone opening has evolved to adjust to varying environmental conditions based on location and/or wild fire occurrence (Keeley, 2012;Przybylski et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The process of initial opening is ecologically relevant, as it influences the dispersal of the mostly airborne seeds and, ultimately, the survival rate of seedlings ( Winsa, 1995 ; Przybylski et al., 2021 ). As Pinus is widespread in the Northern Hemisphere, control of cone opening has evolved to adjust to varying environmental conditions based on location and/or wild fire occurrence ( Keeley, 2012 ; Przybylski et al., 2021 ). In order to understand the parameters affecting opening, we investigated this process exemplary in Scots pine ( Pinus sylvestris ).…”
Section: Introductionmentioning
confidence: 99%
“…The scientific team of Przybylski et al [10] addressed the potential regenerative capacity of Scots pine (Pinus sylvestris) in Central and Eastern Europe. They found that Scots pine trees retained the ability to produce healthy and germinating seeds into old age.…”
mentioning
confidence: 99%